Analysis of Clinical Nurses’ Happiness Levels Using the Oxford Happiness Questionnaire in a Hospital - Risnawati Risnawati; Julida Julida (PT.Mantaya Idea Batara, 2026)
Background: Nurses’ happiness is a critical determinant of job satisfaction and quality of care. Adverse working conditions, shift schedules, and heavy workloads can diminish nurses’ happiness. Objective: Identifying the level of happiness and its primary contributing factors among clinical nurses is therefore essential. Methods: This study utilized a descriptive quantitative approach with the Oxford Happiness Questionnaire. Seventy-three clinical nurses from five inpatient wards at Hasanuddin University Hospital in Makassar were selected through purposive sampling. Results: Most respondents reported a very high level of happiness (87.7%), while 12.3% reported a high level. The most significant contributing aspect was the perception that